Acute Human Toxicity of Macrocyclic Lactones - Yang, Chen-Chang (Current Pharmaceutical Biotechnology, 2012)
Macrocyclic lactones, including avermectins and milbemycins, are novel parasiticides and insecticides that are produced through fermentation by soil-dwelling microorganisms. Although various macrocyclic lactones may differ in their potency and safety, all of them are believed to share common pharmacologic/toxicologic mechanisms, i.e. leading to paralysis and death of parasites and other target organisms via the activation of a glutamate-gated chloride channel in the invertebrate nerve and muscle cells and/or through the effect on gamma-aminobutyric acid (GABA) receptors. Ivermectin is the first macrocyclic lactone that was released for use in both animals and humans, and has demonstrated both excellent efficacy and high tolerability in the treatment of parasite infestations. Other macrocyclic lactones, such as abamectin, emamectin, and moxidectin were subsequently commercialized and have been used as insecticides and acaricides for crop protection or parasiticides for animal health. Although ivermectin therapy is generally well tolerated, adverse effects that are usually transient and mild-to-moderate can occur. Severe adverse effects are rare and can generally be effectively controlled by symptomatic measures. Non-therapeutic exposures to ivermectin and other macrocyclic lactones may also result in toxic effects; significant toxicity however probably develops only after large amount of oral ingestion. Although the exact mechanisms remain unclear, macrocyclic lactones in large doses may pass through the blood-brain barrier (BBB) to produce GABA-mimetic toxic effects. Severely poisoned patients usually present with coma, hypotension, respiratory failure, and even death. Despite the lack of specific therapy, the prognosis is likely to be favorable unless the poisoned patients are complicated with severe hypotension or respiratory failure.
Keywords: Avermectin